2016
DOI: 10.1016/s2095-3119(16)61428-4
|View full text |Cite
|
Sign up to set email alerts
|

Increased sink capacity enhances C and N assimilation under drought and elevated CO2 conditions in maize

Abstract: The maintenance of rapid growth under conditions of CO 2 enrichment is directly related to the capacity of new leaves to use or store the additional assimilated carbon (C) and nitrogen (N). Under drought conditions, however, less is known about C and N transport in C 4 plants and the contributions of these processes to new foliar growth. We measured the patterns of C and N accumulation in maize (Zea mays L.) seedlings using 13 C and 15 N as tracers in CO 2 climate chambers (380 or 750 µmol mol-1) under a mild … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Additionally, the study found that elevated [CO 2 ] allowed more photosynthetic products to be stored in the form of soluble sugars when winter wheat plants were subjected to water deficiency (Figure 3; Table 4), which may indicate that elevated CO 2 concentrations from 400 mmol mol -1 to 800 mmol mol -1 favored Rubisco carboxylation rather than RuBP regeneration (Xu, 2015) may also partially explain that the biomass was barely affected (Wong, 1990;Zheng et al, 2018). Meanwhile, the nitrogen content in the leaves was not limited by elevated [CO 2 ] and water deficiency, which ensured photosynthesis (Zong and Shangguan, 2016). Furthermore, we also found elevated [CO 2 ] concentrations alleviated photosynthesis probably associated with elevated Rubisco activity as well as the amount of gene expression in RbcL3 and RbcS2 when plant under water deficiency (Parry et al, 2003;Hou et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the study found that elevated [CO 2 ] allowed more photosynthetic products to be stored in the form of soluble sugars when winter wheat plants were subjected to water deficiency (Figure 3; Table 4), which may indicate that elevated CO 2 concentrations from 400 mmol mol -1 to 800 mmol mol -1 favored Rubisco carboxylation rather than RuBP regeneration (Xu, 2015) may also partially explain that the biomass was barely affected (Wong, 1990;Zheng et al, 2018). Meanwhile, the nitrogen content in the leaves was not limited by elevated [CO 2 ] and water deficiency, which ensured photosynthesis (Zong and Shangguan, 2016). Furthermore, we also found elevated [CO 2 ] concentrations alleviated photosynthesis probably associated with elevated Rubisco activity as well as the amount of gene expression in RbcL3 and RbcS2 when plant under water deficiency (Parry et al, 2003;Hou et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Under elevated CO 2 conditions, the activity and activation of Rubisco (measured as V cmax and V cm-m ) were both decreased and further caused the downregulation of photosynthesis under low nitrogen conditions [40]. The reason for these declines was that prolonged exposure to high concentrations of CO 2 led to decreased levels of transcripts of proteins involved in photosynthesis [41]. Meanwhile, the decreased electron transport components (measured as J max ) limited the improvement of the photosynthetic rate under elevated CO 2 conditions, indicating a low-level activity of the PSII reaction center [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…After the canopies were sealed into the chamber, the soda‐lime trap was started and once [CO 2 ] was approximating zero (trapped by soda lime) after 1 h, 13 CO 2 was generated by the addition of H 2 SO 4 as described elsewhere (Bromand et al , 2001). The 13 CO 2 concentrations were maintained at the chamber growth conditions of the plants, that is, 400 ± 10 or 700 ± 10 ppm, respectively (Palta et al , 1994; Zong & Shangguan, 2016) by continuously adjusting the emission and ventilation of 13 CO 2 inside the chambers. [CO 2 ] inside the chamber was monitored and recorded during the labelling period with an infrared gas analyser (IRGA, Li‐6400; Li‐Cor Inc., Lincoln, NE, USA) (Fig.…”
Section: Methodsmentioning
confidence: 99%